Black carbon over an urban atmosphere in northern peninsular Southeast Asia: Characteristics, source apportionment, and associated health risks - Shantanu Kumar Pani (2020)
© 2020 Elsevier Ltd Black carbon (BC) has been demonstrated to pose significant negative impacts on climate and human health. Equivalent BC (EBC) measurements were conducted using a 7-wavelength aethalometer, from March to May 2016, over an urban atmosphere, viz., Chiang Mai (98.957°E, 18.795°N, 373 m above sea level), Thailand in northern peninsular Southeast Asia. Daily variations in aerosol light absorption were mainly governed by open fire activities in the region. The mean mass-specific absorption cross-section (MAC) value of EBC at 880 nm was estimated to be 9.3 m2 g−1. The median EBC mass concentration was the highest in March (3.3 μg m−3) due to biomass-burning (comprised of forest fire and agricultural burning) emissions accompanied by urban air pollution within the planetary boundary layer under favorable meteorological conditions. Daily mean absorption Ångström exponent (AAE470/950) varied between 1.3 and 1.7 and could be due to variations in EBC emission sources and atmospheric mixing processes. EBC source apportionment results revealed that biomass-burning contributed significantly more to total EBC concentrations (34–92%) as compared to fossil-fuel (traffic emissions). Health risk estimates of EBC in relation to different health outcomes were assessed in terms of passive cigarette equivalence, highlighting the considerable health effects associated with exposure to EBC levels. As a necessary action, the reduction of EBC emissions would promote considerable climate and health co-benefits.